Myocardial Extracellular Volume Fraction Allows Differentiation of Reversible Versus Irreversible Myocardial Damage and Prediction of Adverse Left Ventricular Remodeling of ST‐Elevation Myocardial Infarction - Chen, Bing‐Hua; An, Dong‐Aolei; He, Jie; Xu, Jian‐Rong; Wu, Lian‐Ming; Pu, Jun (Journal of magnetic resonance imaging, 2020)
Background The relationship between dynamic changes of myocardial injury in ST‐elevation myocardial infarction (STEMI) patients and long‐term prognosis is still unclear. Purpose To evaluate the extracellular volume fraction (ECV) in the differentiation of reversible from irreversible myocardial injury and the prediction value of left ventricular adverse remodeling in patients with STEMI after reperfusion. Study Type Prospective. Population Twenty‐four STEMI patients after reperfusion were included Field Strength/Sequence 3.0 T, T1 mapping, ECV, T2‐STIR, and late gadolinium enhancement (LGE). Assessment All the patients underwent cardiac MRI at four timepoints (days 1, 3, and 7, and at 6 months). The regions of interest (ROIs) were selected at the infarcted myocardium (with/without intramyocardial hemorrhage [IMH] and microvascular obstruction [MVO]). Statistical Tests One‐way analysis of variance and the Kruskal–Wallis test were used for the statistical analysis. Results Native T1 of MI (without MVO/IMH) gradually decreased after reperfusion (P < 0.05). The ECV of MI increased during the first 3 days and then slowly declined. Native T1 of MI with MVO/IMH was the lowest (1184 msec; 1108.5–1266), while ECV (78%; 65.5–87%) was the highest, P < 0.001. Native T1 and ECV of salvageable myocardium were higher than those of the remote myocardium but lower than those of the MI without MVO or IMH (P < 0.001). ROC analysis revealed an area under the curve (AUC) of ECV (0.85, P < 0.001) for differentiating infarcted and salvageable myocardium was higher than that of native T1 mapping (AUC: 0.63, P < 0.001) in the first week after STEMI (P < 0.0001). T1 and ECV differed significantly between patients with and without left ventricle adverse remodeling (P < 0.05). Data Conclusion Dynamic temporal changes in reversibly and irreversibly damaged myocardia were differentiated via native T1 and ECV mapping after primary percutaneous coronary intervention in STEMI patients. ECV may better reflect microvascular injury severity and myocardial viability. MI with higher native T1 and ECV or with severe microvascular injury (MVO and IMH) was correlated with adverse LV remodeling. Level of Evidence: 2 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020. J. Magn. Reson. Imaging 2020;52:476–487.